Voters’ Education and the Outcome of the 2023 General Elections in Nigeria - Berebon, Charles (Universitas Negeri Makassar, 2023)
This study explores the influence of voters’ attitudes and behaviors on the outcome of Nigeria’s 2023 presidential election. The primary objective was to examine how voter disposition impacted the election process and results. A qualitative secondary research methodology was employed, utilizing a grounded theory approach to inquiry. The theoretical foundation for the analysis was the Rational Choice Theory (RCT), which provided insights into voter decision-making processes. The research highlighted that voter mobilization played a crucial role in shaping electoral outcomes. Effective voter education initiatives, along with promises by the Independent National Electoral Commission (INEC) to deploy advanced technology, significantly encouraged voter participation. These technologies included the INEC Voter Enrollment Device (IVED), the Bimodal Voter Accreditation System (BVAS) for voter verification and real-time result transmission, and the INEC Results Viewing (IReV) portal, which allowed public access to polling unit results. However, despite these efforts, the findings revealed that INEC did not fully adhere to its technological commitments and altered established protocols during the election process, leading to public discontent. The study recommends a review of the 2022 Amended Electoral Act to ensure a consistent and mandatory application of technology in all aspects of the electoral process. Additionally, the adoption of e-voting systems, including e-ballots, should be considered to facilitate voting from any location for registered voters and to enable diaspora participation in Nigeria’s elections.